The impact of demographic change on public debt rates in the Eurozone - Barreiro, Filipa Esteves (2024)
This dissertation primarily investigates the relationship between public debt (DP), social spending (DS), and the elderly population (PI) in Eurozone countries, while also considering the influence of additional macroeconomic variables, including 10-year bond interest rates (TXj), the savings rate (NSP), and the inflation rate (INF). The analysis delves into how these variables interact and impact the sustainability of public debt amid economic uncertainties, particularly in the wake of financial crises and the ongoing repercussions of the COVID-19 pandemic. A range of quantitative techniques was employed, starting with Pearson's correlation coefficient to explore the nature of associations among the variables. Subsequently, linear regression analyses were conducted to assess the impact of individual variables on public debt. An Ordinary Least Squares (OLS) model was then utilized to evaluate the collective effects of all variables. Fixed and random effects models were also considered, with the Hausman test aiding in the determination of the most suitable model. The findings reveal that social spending and GDP positively affect public debt, while inflation displays a negative correlation with it. Notably, this suggests that moderate inflation may play a role in mitigating debt burdens. Furthermore, interest rates on 10-year bonds were identified as significant factors influencing public debt dynamics. Overall, this study contributes valuable insights into the complexities of public debt in the Eurozone and lays the groundwork for further research on similar macroeconomic relationships in other contexts, despite limitations such as the exclusion of specific institutional factors. The research holds significant implications for the formulation of sustainable fiscal policies in an era characterized by rising levels of public debt globally.